2020
DOI: 10.2355/isijinternational.isijint-2019-636
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved and <i>In-situ</i> Observation of <i>δ</i>–<i>γ</i> Transformation during Unidirectional Solidification in Fe–C Alloys

Abstract: Time-resolved and in-situ observations using synchrotron radiation X-rays successfully proved that a massive-like transformation, in which the γ phase was produced through the solid-solid transformation and partitioning of substitute elements such as Mn and Si at the δ-γ interface was negligible, was selected in the unidirectional solidification of 0.3 mass% C steel at a pulling rate of 50 μm/s. The massive-like transformation produced fine γ grains near the front of the δ-γ interface. The coarse γ grains also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A selection of the massive-like transformation was confirmed in 1-mm-thick bulk specimens. 62) Undercooling for nucleation of the γ phase was smaller compared with undercooling in 100-μm-thick specimens. Thus, the specimen dimension influences undercooling for γ-phase nucleation, but a massive-like transformation was still selected and undercooling was required for nucleation of the γ phase even in the bulk specimens.…”
Section: Massive-like Transformation As a Transient Phenomenonmentioning
confidence: 87%
See 2 more Smart Citations
“…A selection of the massive-like transformation was confirmed in 1-mm-thick bulk specimens. 62) Undercooling for nucleation of the γ phase was smaller compared with undercooling in 100-μm-thick specimens. Thus, the specimen dimension influences undercooling for γ-phase nucleation, but a massive-like transformation was still selected and undercooling was required for nucleation of the γ phase even in the bulk specimens.…”
Section: Massive-like Transformation As a Transient Phenomenonmentioning
confidence: 87%
“…In the early stage, solidification in Sn, Al and Mg alloys was observed in-situ by X-ray transmission imaging (twodimensional imaging). [29][30][31][32][33] Later, the further-developed apparatus allowed for the observation of Cu, Ni, and Fe alloy solidification above 1 300 K. 21,[34][35][36][37][38] Transmission imaging was combined with X-ray diffraction (XRD) measurements. Figure 1(a) shows a typical setup for transmission imaging with XRD.…”
Section: X-ray Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…20) In addition, the massive-like transformation can be selected from the surface to the center in the continuous casting of Fe-based alloys. 21) Therefore, mechanism of the massive-like transformation is an interesting phenomenon. The isotopic transformation from α phase to γ phase in Ti-based alloys and the isotopic transformation from δ phase to γ phase in Fe-based alloys are essentially the same cannot be concluded from the present observations.…”
Section: Characteristics Of α-γ Transformationmentioning
confidence: 99%
“…It started with the observation of low-melting-point alloys such as Al, Sn, and Zn alloys, [8][9][10][11][12] and now it is possible to observe a wide range of alloys with high melting points such as Fe-based alloys. [13][14][15][16][17][18][19][20][21] For example, it is found that the peritectic solidification, which has been considered to be the conventional is not selected in Fe-C alloys, 16,17) which increases the significance of insitu observation of solidification from both academic and industrial perspectives.…”
Section: Introductionmentioning
confidence: 99%